An Applied Research in Properties and Clinical Application of Bone Marrow of Mesenchymal Stem Cells - Zahra Barzkar; Mohammadhosein Karimi; Zohre Makoolati; Gholamreza Kaka; Majid Naghdi (Fasa University of Medical Sciences, 2015)
In the last 15 years, there has been a significant increase in the number of researchers interested in studying Mesenchymal Stem Cells (MSCs). MSCs are self-renewing, heterogenic, and multipotent cells that have multi-lineage potential to differentiate not only in to cell types of mesodermal origin but also other various cell lineage MSCs migrate to inflammatory tissues and apply immunosuppressive effects. The usages of these cells as diagnostic tool, secretor of some growth factors and cytokines, gene expresser of engineered cells, and other characteristics such as relatively easy preparation and proliferation, add to the attraction of these cells. Scientists suggest that the transplantation of these cells is a proper alternative for treatment of some incurable illnesses of bone, heart, skin, and liver such as diabetes. However, these kinds of treatment, not clearly associated with the definitive remedial results, are going on in an additive manner. Introducing stem cells with their miracle properties as a predictive precipitance and their curative potential in the recent years, led to many questions, concerns, and expectations regarding this newly proposed therapeutic method. Nowadays, knowing the true extent of the curative effect of these cells, especially in some tissues more clearly reduces concerns and makes expectations more rational like other treatments.